Effect of Arbutus andrachne L. methanolic leaf extract on TRPV1 function: Experimental and molecular docking studies - Sahar Jaffal, Sawsan Oran, Mohammad Alsalem, Belal Al-Najjar (Journal of Applied Pharmaceutical Science, 2022)
Currently used analgesics have several side effects urging the need for new natural sources of therapeutics. Transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel and a key receptor in pain. In this study, we explored the effect of a methanolic leaf extract from Arbutus andrachne L. (a medicinal plant growing in Jordan) and its mechanism of action on TRPV1 function and expression. Our findings showed that the extract decreased capsaicin-induced cobalt (Co+2) influx in dorsal root ganglia (DRG) neurons, an effect that involved cannabinoid receptor 1 (CB1) and TRPV1 but not alpha (α)-2 adrenergic receptors. The extract had no effect on capsaicin-evoked TRPV1 expression in the skin, DRGs, spinal cord, and brain. Importantly, the effect of A. andrachne was similar to the responses shown in the positive control group. Additionally, by conducting molecular docking between the ingredients identified in A. andrachne extract and TRPV1 receptor, it was found that α-tocopherol, ursolic acid, and β-sitosterol (similar to TRPV1 antagonist, capsazepine) fit in the same pocket of TRPV1 receptor indicating that these compounds are the active ingredients responsible for the effect of the extract in decreasing capsaicin-induced Co+2 influx. A. andrachne extract decreased capsaicin-induced Co+2 influx significantly and can be a good candidate as an analgesic.
Keywords: Arbutus andrachne, TRPV1, Co+2 influx, expression, molecular docking, active constituents